STANDAR KUALITAS KOMPETENSI KONSELOR PROFESIONAL : Studi Pengembangan Standar Kompetensi di Lingkungan Pakar Konseling Perguruan Tinggi Negeri dan Konselor SMA Negeri - Murad, Abdul (2005)
ABSTRACT The Quality Standard of Professional Counselor Competences Many unsatisfied expressions of the counseling service users towards counselor's and guidance teachers performance in our society and later research results in general support these indications by discovering fact that a lot of parents (38 %) did not admit the significance of guidance and counseling program existence because of a shortage of professionals guidance teachers in implementing or performing their duties (Dedi Supriadi, 1990). Through writer's preliminarily study towards guidance teachers in SMAN IV and SMAN II in Medan, was founded that a lot of counselors showed non professional attitudes/behaviors and known that they do not have educational backgrounds of guidance and counseling, but subject teachers that had been given responsibility to perform guidance and counseling service. Some efforts had been incorporated to promote the guidance teachers performance, such as through seminars, trainings, But, those result were clearly not measured yet, because there was not competence standard at the time yet. Process to produce standard had still been going on ABKIN convention in Semarang from April, 13 up to April, 16, 2005 until now. To control counseling service quality, was needed competence standard to evaluate what level of competency had actually been reached and how high the performance was expected to be able to increase up to threshold standards level. The common goal of this research is to discover a standard of professional counselor competence in Indonesia. Specifically, this research was purposed to find empirical proof about the actual performance level of professional counselor competence, and to describe the threshold standards level of the professional counselor performance. This research was performed by applying research and development (R & D) method combined with Delphi technique and Benchmarking Study (a process to analyze information about the actual performance and the ideal one for the improvement of performance quality). R & D approach and Delphi technique were applied to produce the ultimate standard of professional counselor competence in Indonesia, whereas benchmarking study was used to attain an empirical information about the expected minimum achievement level. The Subjects of research were 64 counselors in SMAN and 30 guidance and counseling experts that was taken in the way of purposive sampling of the counselor working in 12 SMAN in Bandung, SMAN in Malang, and SMAN in Padang. The research data (data about the actual performance of counselor and expert judgment about competence) were collected through questionnaire and interview instruments, and analyzed statistically through nonparametric technique. Data analysis was performed by applying frequency, percentage (the actual score of ideal score). Finally, five results had been produced from this research, namely: (1) the actual performance level of professional counselor competence holistically was at medium level (67.61%); (2) the actual performance level of professional counselor competence from counseling background was at high level (70.13%); whereas counselors with non-counseling background were at medium (63,67%); (3) classification on professional counselor competence in core, specific and common competence and also rationalization of its relevance each dimensions of professional counselor competence; (4) the condition of the expected threshold standards level; (5) the ultimate standard of professional counselor competence in Indonesia. Some recommendations are contributed for policy maker (DIKNAS, LPTK, ABKIN), counselors and the following researchers.